INFLUENCE OF HEALTH SEEKING BEHAVIOUR ON GLYCEMIC CONTROL AMONG TYPE 2 DIABETES MELLITUS FEMALE PATIENTS AGED 35-60 YEARS IN TAVETA SUB-COUNTY HOSPITAL - Nyong'a, Lucy Phelister; Mugo, Judy W.; Suleiman, Mbaruk A. (Journal of Health, Medicine and Nursing, 2022)
Purpose: The study aimed to assess the effect of the health seeking behaviour on glycemic control among type 2 diabetes mellitus female patients aged 35-60 years in Taveta sub-County Hospital. Methodology: A descriptive cross sectional design was adopted and systematic random sampling technique used to select 135 study subjects comprising of T2DM female patients aged 35-60 years who are registered at Taveta sub-County hospital diabetes outpatient clinic. Quantitative data was collected from informed consenting T2DM female patients using researcher administered structured questionnaire for health seeking behaviour factors, and glycemic control. The fasting blood sugar readings obtained from the patients' self blood sugar monitoring cards was used to establish glycemic control. Quantitative data was analyzed using Statistical Package for Social Scientists (SPSS) Version 22. Findings: The odd of having a good glycemic control is 1.416 times higher for environment of the diabetes clinic room/area that is clean as compared to environment of the diabetes clinic room/area that is somewhat clean. The most used method to control glucose is the herbal remedies to manage diabetes. Unique contribution to theory, practice and policy: The patients should attend to all scheduled clinic check-ups to get the health care personnel and nutritionists counsel the patients based on the progress assessment. The patients should moreover keep the progress communicated to the health officers when there are changes in their sugar levels. The monitoring of blood sugar should be done regularly. It is recommended for an increase in scope for creation of diabetic awareness and reach out to the patients and community.